Clinical examination in the OSCE era: are we maintaining the balance between OS and CE?. Issue 1099 (16th February 2017) - Lafleur, Alexandre; Leppink, Jimmie; Côté, Luc
ABSTRACT: After more than three decades of assessment of clinical competence through Objective Structured Clinical Examinations (OSCEs), are medical trainees viewing clinical examination through the lens of an assessment method? Has the structure (the OS) become more important than the skill itself (the CE)? For many students, the standards required by OSCEs are the skills expected for clinical competence. Most recent textbooks on clinical examination are based on the structure needed to succeed in an OSCE, but OSCEs were not designed to teach an ideal framework for performing a clinical examination and most medical encounters require a more flexible patient-centred approach. How can we ascertain that medical students are focusing less on the OS and more on learning 'the art' of CE?